Can a Simple Static-Equivalent Model Be Used to Predict Major Trends in the Dynamic Structural Response of Monopile Offshore Wind Turbines? - Antonio J. Romero-Monzón; Carlos Romero-Sánchez; Guillermo M. Álamo; Luis A. Padrón (Applied Sciences)
This paper tests the capability of a simplified model to predict major trends in the dynamic structural response of monopile offshore wind turbines. For this purpose, the results of two numerical models of different levels of complexity are compared: the advanced time-domain multi-physics tool OpenFAST and a simplified static-equivalent model based on beam elements and concentrated masses. The IEA-15-240-RWT reference wind turbine is considered as a benchmarking problem. The comparison between the two structural models is presented in terms of their fundamental frequencies and through the analysis of shear forces and bending moments under wind-only and combined wave and wind load scenarios. The results show that the simplified model can adequately represent the system’s mass and stiffness characteristics, as well as the impact of soil–structure interaction effects on its fundamental frequency. Turbulence and wind velocity have a significant impact on internal forces and on the ability of the simplified model to reproduce their values. Despite the large differences obtained for highly turbulent scenarios, the acceptable accuracy obtained for relevant load scenarios and the conservative nature of the simplified model make it a viable option for preliminary large-scale studies that prioritize efficiency and efficacy over high-precision.